Effectiveness of Couples Coping Enhancement Training on Resilience and Marital Conflict During the Transition to Parenthood - Hasanzadeh, Marzieh; Samavati, Mehdi; Javaheri, Abbas (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The purpose of this study was to determine the effectiveness of Couples Coping Enhancement Training (CCET) on resilience and marital conflicts in couples during the transition to parenthood.Methods: This quasi-experimental research employed a pre-test, post-test, and follow-up design with experimental and control groups. The population consisted of couples attending counseling centers in Shiraz in 2022, from whom 12 couples were selected using a volunteer-available sampling method based on inclusion and exclusion criteria and randomly assigned to either the experimental group (6 couples with training) or the control group (6 couples without training). The CCET training sessions for the experimental group were conducted over nine weekly two-hour sessions. Data were collected using the Connor-Davidson Resilience Scale (Connor & Davidson, 2003) and the Sanaei Zaker and Barati Marital Conflict Questionnaire (2008). The data were analysed with analysis of variance with repeated measurements method using SPSS-25 software.Findings: Data were analyzed using repeated measures analysis of variance in SPSS26. The findings indicated that CCET significantly enhanced resilience and reduced marital conflicts in the experimental group compared to the control group in the post-test. Furthermore, the non-significant difference between post-test and follow-up scores in the experimental group suggests the lasting impact of CCET on resilience and marital conflicts in couples during the transition to parenthood.Conclusion: Therefore, CCET can be utilized to increase resilience among couples and aid in reducing marital conflicts post-childbirth.